2012
DOI: 10.1111/j.1748-1716.2012.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against L‐NAME‐induced reduction in cardiac output persists even after cessation of angiotensin‐converting enzyme inhibitor treatment

Abstract: Despite equivalent impact on MAP and incidence of myocardial infarction, prior enalapril treatment resulted in the preservation of cardiac function following L-NAME. Understanding the mechanisms by which transient ACE inhibition protects against reductions in cardiac function in the absence of ongoing treatment may reveal novel targets for heart failure treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…This finding is in agreement with those of several studies, which have indicated that L-NAME decreases the CO in a normal level of Hct either in the short-term or long-term treatments with L-NAME 25)27)28). Furthermore, in this study, the L-NAME administration led to a reduction in SV even after hemodilution.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with those of several studies, which have indicated that L-NAME decreases the CO in a normal level of Hct either in the short-term or long-term treatments with L-NAME 25)27)28). Furthermore, in this study, the L-NAME administration led to a reduction in SV even after hemodilution.…”
Section: Discussionsupporting
confidence: 94%
“…By administration through a coronary catheter, using non-selective NOS inhibitors such as N-nitro-L-arginine (L-NNA) in normal dogs an increment in the coronary blood flow was shown 29). In contrast, Biwer et al28) demonstrated that long-term L-NAME-treated rats had not only a decrease in CO and SW but also a decrease in coronary blood flow, which potentially caused cardiac dysfunction. Therefore, it is a point of concern that using PEs in hemodilution with a stage of NOS impairment can lead to an attenuation of the cardiac compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to species differences or that the vessels used in the present study are from more distal regions of the vasculature or that the transient nature in vivo is caused by a stimulus which is not present in the ex vivo setting. This opportunity to study ANG II vasoregulation ex vivo may be valuable, as its blockade prevents the chronic effects of long-term nitric oxide synthase inhibition (Biwer et al 2013), a fascinating phenomenon which has also been observed in the kidney (Helle et al 2009(Helle et al , 2010. We were able to harvest about 10 arterioles from each dissected right ventricle; all positively identified as pre-capillary by attached capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a transient ACE inhibitor treatment induced protective effects that persisted even after stopping treatment and restoration of the renin-angiotensin system. Importantly, NOS inhibition induced focal regions of cardiomyocyte loss as well as coronary artery injury in both naïve and previously treated rats (3). Thus, the reduction in inflammation and fibrosis in rats previously treated with an ACE inhibitor appears to reflect a modified response to myocardial injury.…”
mentioning
confidence: 86%
“…It has thus been suggested that targeting fibroblast survival may be a mechanism by which these drugs are effective in limiting cardiac fibrosis. We have shown that prior transient (i.e., 2-wk treatment followed by a 2-wk washout period) ACE inhibition in young adult male SHRs to be protected against a future cardiac insult induced by the nonspecific NOS inhibitor N -nitro-L-arginine methyl ester (L-NAME) (3,13). This protection was characterized by a preservation of cardiac output (3), a reduction in outer wall collagen deposition, and decreased densities of proliferating cells and macrophages in the LVs of rats that had been previously treated with an ACE inhibitor (13).…”
mentioning
confidence: 99%